Maternal and perinatal outcome in Rh-Negative women - Yadav, Munjal; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To find out the Maternal and perinatal outcomes in Rh-Negative mothers. Methods: This is a cross sectional study of all Rhesus negative mothers giving childbirth at Department of Obstetrics and Gynecology, Nobel Medical College Teaching Hospital from March 2020 to February 2021. Maternal variables like age, parity, mode of delivery, and complications were recorded. Fetal vari- ables like period of gestation, fetal outcomes, hemoglobin, indirect bilirubin, fetal weight were noted. Results: There were 108 cases of Rh negative pregnancy and 95 of them deliv- ered Rh positive fetuses. Prevalence of Rh negative pregnancy was 1.68%. Half of them (51; 53.6%) underwent caesarean section due to obstetric indications with 20 repeat cesarean sections and 9 (17.7%) cases for fetal distress. Gross perinatal death was 9; none of the patients received antepartum im- munoprophylaxis; and 86 received postpartum Anti-D Rh IgG. There was only one case of proven isoimmunisation presented as hydrops fetalis in a grand multiparous woman with positive Indirect Coomb Test; and two newborn re- ceived exchanged transfusion. Conclusion: Rhesus negative rate was 1.68% and proven isoimmunization rate was 1%.